Penyuluhan tentang Eating Disorder guna Meningkatkan Pengetahuan Mahasiswa Universitas Trunojoyo Madura - Nuraini, Dyah; Setiawan, Alex Andre; Aldelia, Dini (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Eating disorders is a disorders related to abnormal and persistent eating behaviours that affect eating consumption patterns. There are various eating disorders such as anorexia nervosa, bulimia nervosa, and binge eating. It can be caused by various factors such as genetic, psychological, socio-cultural, environmental. Students are one of the people who often experience eating disorders because of the many pressures that disrupt eating patterns such as academic stress or body image. The purpose of this activity is to provide information and understanding related to eating disorders in order to increase knowledge in Trunojoyo Madura University students. The method used is by counselling students by giving pre-test questions for 10 minutes, then continued with a 20-minute material explanation, a 10-minute discussion session, and the last post-test for 10 minutes. The results of the pre-test were 39.63% and the post-test was 65.13%, these results showed that there were differences after and after the provision of material. Community service activities regarding eating disorder material counselling can provide benefits and influence for Trunojoyo Madura University students to increase knowledge.